Analysis of factors that influence the occurrence of otitis media with effusion in pediatric patients with adenoid hypertrophy - Chen, Wenjing; Yin, Guoping; Chen, Yijing; Wang, Lijun; Wang, Yingying; Zhao, Chunmei; Wang, Wan; Ye, Jingying (Frontiers in Pediatrics, 2023)
Objective: Adenoid hypertrophy (AH) and otitis media with effusion (OME) are common pediatric otolaryngological diseases and often occur concurrently. The purpose of this study was to comprehensively analyze the factors that influence the occurrence of OME pediatric patients with AH. Methods: Patients younger than 12 years with AH, who were hospitalized for treatment at Beijing Tsinghua Changgung Hospital in Beijing, China, between March 2018 and February 2022 were included. The patients were divided into an AH group and an AH+OME group based on the presence of OME. The authors collected the following clinical data for univariable analysis: sex; age; body mass index (BMI); comorbid nasal congestion/rhinorrhea, recurrent tonsillitis, or allergic rhinitis (AR); adenoid and tonsil grade; tonsillar hypertrophy; food/drug allergy; history of adenoidectomy and congenital diseases; breastfeeding status; preterm birth; exposure to environmental tobacco smoke (ETS); family history of adenotonsillectomy, otitis media, and AR; main data of polysomnography and oropharyngeal conditional pathogen culture data of some patients. Univariate analysis was performed as a basis for logistic regression analysis. Results: A total of 511 children (329 boys and 182 girls) were included, their mean age was 5.37±2.10 years. Of them, 407 (76.6%) were in the AH group and 104 (20.4%) in the AH+OME group. Univariate analysis revealed statistically significant differences in age, BMI, adenoid grade, AR, breastfeeding status, and ETS exposure between the two groups. Multivariate stepwise logistic regression analysis showed that age, adenoid grade, AR, breastfeeding status, and ETS influenced the occurrence of OME in pediatric patients with AH. The risk of OME decreased with increasing age. High adenoid grade, ETS exposure, and comorbid AR were risk factors for OME in pediatric patients with AH, but breastfeeding was a protective factor. The final analytical results of the oropharyngeal conditional pathogen culture data showed that Streptococcus pneumoniae positivity was associated with OME in AH. Conclusion: The pathogenesis of AH with OME is complex. Young age, high adenoid grade, ETS exposure, non-breastfed status, comorbid AR, and the presence of S. pneumoniae in the oropharynx are risk factors for OME in pediatric patients with AH.